The Influence of Perception of Learning Media and Learning Motivation on Social Science Learning Achievement at Private Junior High Schools in South Jakarta City - Marlina, Reni (Indo Consultan Energi, 2025)
Study This aiming For analyze and test truth hypothesis about Influence Perception Students on Learning Media and Motivation Study To Performance Study Knowledge Knowledge Social. Hypothesis study includes : 1) There is significant influence​ perception on learning and motivation media Study to performance learning social studies. 2) There are significant influence​ perception on learning media to performance learning social studies. 3) There are significant influence​ motivation Study to performance study social studies. Research This done with survey method. Population is students / i Private Mts in South Jakarta with big sample as many as 70 students , sample scrambled with use random sampling technique with method raffle. Instrument study with questionnaires, tests, and documents. And have tested shown with all mark asymp, sign > 0.05. This is means the data is normally distributed. Data analysis using Analysis of variance (ANOVA) two path / direction. This is proven with acquisition of Sig. 0.00 < 0.05 and F h = 98.93. 2) Yes significant influence​ perception on learning media to performance study social studies for students of private MTs in South Jakarta. This is proven with acquisition of Sig. 0.00 < 0.05 and t h = 3.246. 3) Yes significant influence​ motivation Study in a way together to performance learning social studies for private Mts students in South Jakarta. This is proven with testing hypothesis obtained Sig. 0.00 < 0.05 and t h = 4.070. The results of the study This useful for teachers, administrators institution education For increase quality of learning media and motivation Study student to performance learning social studies at the Mts level Private